2020
DOI: 10.1177/1461445620940051
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of danmu: Coherence in massive anonymous chats on Bilibili.com

Abstract: Although coherence has been widely studied in computer-mediated communication (CMC), insufficient attention has been paid to emergent multimodal forms. This study analyzes a popular commentary system on Chinese and Japanese video-sharing sites – known as danmu or danmaku – where anonymous comments are superimposed on and scroll across the video frame. Through content and multimodal discourse analysis, we unpack danmu-mediated communication analyzing the newest interface (on Bilibili.com), the comments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…The present study identified a number of types of online video watching that have not been sufficiently investigated in previous studies, including: videos with Danmu comments (i.e., comments floating across the screen while the online video is playing), videos with auto-tune remix-themed content (i.e., videos containing repetitive audio or videos clips usually with funny film editing), and rustic videos (videos with corny jokes usually filmed in the countryside). Danmu comments have previously been studied from a linguistics perspective [ 32 ], but were not associated with potential addictive or problematic internet use. Participants in the present study expressed diverse behaviors towards Danmu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified a number of types of online video watching that have not been sufficiently investigated in previous studies, including: videos with Danmu comments (i.e., comments floating across the screen while the online video is playing), videos with auto-tune remix-themed content (i.e., videos containing repetitive audio or videos clips usually with funny film editing), and rustic videos (videos with corny jokes usually filmed in the countryside). Danmu comments have previously been studied from a linguistics perspective [ 32 ], but were not associated with potential addictive or problematic internet use. Participants in the present study expressed diverse behaviors towards Danmu.…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging Chinese video platform is Bilibili, which contains both short-form videos and other more regular videos. Zhang and Cassany investigated the scrolling commenting system on Bilibili (called ‘Danmu’ comments in Chinese), which float across the online video frame while playing [ 32 ]. They found that video watchers used repetitive or specific expressions and funny words to interact with each other on Danmu while watching.…”
Section: Introductionmentioning
confidence: 99%
“…There are also second person references. However, some users use the incoherence of barrage language for fun (such as "wait for me in front of you" "don't go yet") (Zhang & Daniel, 2020, p.15) [10].…”
Section: Content and Discourse Analysismentioning
confidence: 99%
“…Screen. The love of Bilibili, now, although they have a lot more people watching movies, there used to be no way to watch online, but now there is no point in adding fun [2]. At the same time, Yue went a step further and surveyed 248 Bilibili users in 2021 to collect users' motivations and obstacles to viewing the barrage.…”
Section: Introductionmentioning
confidence: 99%